Association Between AZD7442 (Tixagevimab-Cilgavimab) Administration and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection, Hospitalization, and Mortality. (20th August 2022) - Kertes, Jennifer; Shapiro Ben David, Shirley; Engel-Zohar, Noya; Rosen, Keren; Hemo, Beatriz; Kantor, Avner; Adler, Limor; Shamir Stein, Naama; Mizrahi Reuveni, Miri; Shahar, Arnon
Abstract: Background: Intramuscular AZD7442 (tixagevimab–cilgavimab [Evusheld; AstraZeneca]) has been found effective among immunocompromised individuals (ICIs) in reducing SARS-CoV-2 infection and severe disease in ICIs. We evaluated the association between AZD7442 administration and SARS-CoV-2 infection and severe disease (COVID-19 hospitalization and all-cause mortality) among selected ICIs, during a fifth Omicron-dominated wave of COVID-19 (December 2021–April 2022) in Israel. Methods: ICIs aged ≥12 years identified in the Maccabi HealthCare Services database were invited by SMS/e-mail to receive AZD7442. Demographic information, comorbidities, coronavirus vaccination, and prior SARS-CoV-2 infection and COVID-19 outcome data (infection, severe disease) were extracted from the database. Rates of infection and severe disease were compared between those administered AZD7442 and those who did not respond to the invitation over a 3-month period. Results: Of all 825 ICIs administered AZD7442, 29 (3.5%) became infected with SARS-CoV-2 compared with 308 (7.2%) of 4299 ICIs not administered AZD7442 ( P < .001). After adjustment, the AZD7442 group was half as likely to become infected with SARS-CoV-2 than the nonadministered group (OR: .51; 95% CI: .30–.84). One person in the AZD7442 group (0.1%) was hospitalized for COVID-19 compared with 27 (0.6%) in the nonadministered group ( P = .07). No mortality was recorded among the AZD7442 group compared with 40 deaths (0.9%) in the nonadministered group ( P = .005). After adjustment, ICIs administered AZD7442 were 92% less likely to be hospitalized/die than those not administered AZD7442 (OR: .08; 95% CI: .01–.54). Conclusions: AZD7442 among ICIs may protect against Omicron variant infection and severe disease and should be considered for pre-exposure prophylactic AZD7442. Abstract : Immunocompromised individuals (ICIs) administered AZD7442 had lower adjusted rates of SARS-CoV-2 infection and severe disease (hospitalization and mortality) than an ICI group targeted for AZD7442 who did not present for treatment during an Omicron-dominated infection wave.